Assessment of Quality of Life and Coping Strategies Used by Amputated Patients Attending Orthopedics OPD to Provide Rehabilitation Program: A Descriptive Study - Monika . (International Journal of Orthopedic Nursing and Practices, 2025)
Introduction: Amputation is defined as the surgical removal of a body appendage such as limbs. It has a profound social, economic, physical and psychological impact on patients. Objectives of the study: To assess the quality of life and coping-strategies used by an amputated patient and to determine an association between the quality of life and coping-strategies with selected socio-demographic variables at Pt. B. D. Sharma, PGIMS, Rohtak. Material and Method: A quantitative research approach and descriptive cross-sectional was adopted for the study. WHOQQL-BREF scale and Brief-COPE scale were used for data collection on various dimensions of quality of life and coping-strategies. Results: 40 patients were experiencing very poor and 56 patients were experiencing poor overall quality of life. Coping-strategies utilized by the patients with a predominant use of problem-focused by 50, avoidant by 34 and emotion-focused by 16 patients. There is no significant association between QoL and age, gender, marital status, educational status, occupation, income of the family, place of residence, site of amputation, leg involved, reason for amputation and walking ability but there is a significant association between QoL and use of prosthesis. There is no significant association between coping-strategies and age, gender, marital status, educational status, occupation, the income of the family and place of residence but there is some association between coping-strategies and site of amputation, leg involved, the reason for amputation, use of prosthesis and walking abilities. This study contributes valuable insights to inform the development of targeted rehabilitation programs for amputees attending orthopedics OPD at Pt. B. D. Sharma PGIMS, Rohtak. Conclusion: Quality of life is very poor to poor in amputees in each domain and coping-strategies used by these patients were inadequate. These patients need specific rehabilitation and support to enhance overall well-being and adaptation.
Keywords: Amputation; Assess; Quality of life; Rehabilitation; coping-strategies